2018
DOI: 10.1007/s40430-018-1066-z
|View full text |Cite
|
Sign up to set email alerts
|

An approach for characterizing twin-tube shear-mode magnetorheological damper through coupled FE and CFD analysis

Abstract: The most promising technology in the field of semi-active suspension systems is the use of magnetorheological property of MR fluid, whose material behavior can be controlled through external magnetic field. Devices developed based on this principle are adaptive and controllable as desired for a specific application. It is important to understand the damping characteristics of these devices before employing them, using experimental or computational approaches. In the present work, both experimental and computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…Shivaram and Gangadharan [18] reported that magnetic field strength and volume fraction of the iron particles have a major influence on the damping force and that the selection of damping materials should be based on application as there is a significant dependence of frequency on the damping force. Gurubasavaraju et al [19] characterized a twin-tube MR damper experimentally and found that the experimental results are in good agreement with those obtained using finite element analysis coupled with computational fluid dynamic analysis. Further, they concluded that damping force increases with a decrease in shear flow gap.…”
Section: Introductionmentioning
confidence: 56%
“…Shivaram and Gangadharan [18] reported that magnetic field strength and volume fraction of the iron particles have a major influence on the damping force and that the selection of damping materials should be based on application as there is a significant dependence of frequency on the damping force. Gurubasavaraju et al [19] characterized a twin-tube MR damper experimentally and found that the experimental results are in good agreement with those obtained using finite element analysis coupled with computational fluid dynamic analysis. Further, they concluded that damping force increases with a decrease in shear flow gap.…”
Section: Introductionmentioning
confidence: 56%
“…选 取 对 稳 态 剪 切 下 的 模 拟 精 度 有 重 要 影 响 . Gurubasavaraju等人 [62] 采用CFD方法模拟了磁流变液 阻尼器在不同电流、不同频率下的响应, 计算与实验 相符. 特别地, He等人 [63] 采用CFD方法研究不同形 状、不同质量分数的颗粒的流动阻力系数, 为颗粒动 力学模拟提供理论基础.…”
Section: 指出 成链过程由颗粒体积分数主导 磁场力模型的unclassified
“…Therefore, in order to improve the performance of the MRF damper and to effectively control its damping force, it is necessary that the magnetization properties of the magnetic circuit are considered in the design phase [16,17]. The finite element numerical simulation has become one of the effective ways to solve complex geophysical problems for scientific research and engineering computing [18,19]. During finite element simulation (FES) the interconnections of fields are taken into account in the form of feedback in accordance with the results of the certain fields calculation, in which structural parameters, electromagnetic coil parameters, and material properties of the MRF damper could be analyzed [20,21].…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…where is the magnetic field intensity of MRF. From (13) and (18), the relationship between the current and the magnetic field intensity in the damping gap could be expressed as = 2ℎ (19) As the values of and ℎ in (19) could be found in Table , the magnetic field intensity in the MRF under different current could be calculated by (19). The MRF is under the control of the magnetic field generated by the coil in MRF damper.…”
Section: Magnetic Circuit Optimal Design Of Mrf Dampermentioning
confidence: 99%